Wet-Spun Trojan Horse Cell Constructs for Engineering Muscle - Quigley, Anita F.; Cornock, Rhys; Mysore, Tharun; Foroughi, Javad; Kita, Magdalena; Razal, Joselito M.; Crook, Jeremy; Moulton, Simon E.; Wallace, Gordon G.; Kapsa, Robert M. I. (Frontiers in Chemistry, 2020)
Engineering of 3D regenerative skeletal muscle tissue constructs (skMTCs) using hydrogels containing muscle precursor cells (MPCs) is of potential benefit for repairing Volumetric Muscle Loss (VML) arising from trauma (eg road/industrial accident, war injury) or for restoration of functional muscle mass in disease (eg Muscular Dystrophy, muscle atrophy). Additive Biofabrication (AdBiofab) technologies make possible fabrication of 3D regenerative skMTCs that can be tailored to specific delivery requirements of VML or functional muscle restoration. Whilst 3D printing is useful for printing constructs of many tissue types, the necessity of a balanced compromise between cell type, required construct size and material/fabrication process cyto-compatibility can make the choice of 3D printing a secondary alternative to other biofabrication methods such as wet-spinning. Alternatively, wet-spinning is more amenable to formation of fibres rather than (small) layered 3D-Printed constructs. This study describes the fabrication of biosynthetic alginate fibers containing MPCs and their use for delivery of dystrophin-expressing cells to dystrophic muscle in the mdx mouse model of Duchenne Muscular Dystrophy (DMD) compared to poly(DL-lactic-co-glycolic acid) copolymer (PLA:PLGA) topically-seeded with myoblasts. In addition, this study introduces a novel method by which to create 3D layered wet-spun alginate skMTCs for bulk mass delivery of MPCs to VML lesions. As such, this work introduces the concept of Fibre-MTCs (fMTCs) and 3d Mesh-MTCs (mMTCs) for delivery of regenerative MPCs to diseased and damaged muscle respectively.